Employee Success through the Level of Emotional Intelligence and Spiritual Intelligence - Selviyani, Retno; Wulansari, Nury Ariani (Management Analysis Journal, 2019)
The purpose of this study is to analyse the influence of emotional intelligence and spiritual intelligence on employee performance through work motivation as a mediating variable. The sample in this study amounted to 195 employees. The sampling technique uses probability sampling with the type of proportionate random sampling. The method of collecting data using a questionnaire measured by a likert scale. The analytical method used is descriptive ststistical test and version SmartPLS 3.0 software. The result showed that emotional intelligence has a positive and significant effect on work motivation, and has an effect on employee performance. However, spiritual intelligence does not have an influence on work motivation or employee performance. Work motivation has an influence on employee performance. Work motivation can also mediate the influence of emotional intelligence on employee performance. However, it cannot mediate the influence of spiritual intelligence on employee performance. This research is expected to be an entry for companies to be able to hold training to improve emotional intelligence and intellectual intelligence which is believed to improve employee performance in general banking.